1999
DOI: 10.1902/jop.1999.70.6.632
|View full text |Cite
|
Sign up to set email alerts
|

One Stage Full‐ Versus Partial‐Mouth Disinfection in the Treatment of Chronic Adult or Generalized Early‐Onset Periodontitis. I. Long‐Term Clinical Observations

Abstract: These findings suggest that a one stage full-mouth disinfection results in an improved clinical outcome for the treatment of chronic adult or early-onset periodontitis as compared to scaling and root planing per quadrant at 2-week intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
177
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(202 citation statements)
references
References 81 publications
15
177
3
7
Order By: Relevance
“…Mongardini et al 1999 36 The clinical data were reported in another study that is included (Quirynen et al 2000) 30 Quirynen et al 1995 17 The duration of the study less than six months. However, the long-term follow-up of the patients was reported in another study that is included 31 Quirynen et al 1998 37 Only microbiological data were reported …”
Section: Reason(s) For Exclusionmentioning
confidence: 99%
“…Mongardini et al 1999 36 The clinical data were reported in another study that is included (Quirynen et al 2000) 30 Quirynen et al 1995 17 The duration of the study less than six months. However, the long-term follow-up of the patients was reported in another study that is included 31 Quirynen et al 1998 37 Only microbiological data were reported …”
Section: Reason(s) For Exclusionmentioning
confidence: 99%
“…The assessed clinical parameters at t SRP, with exception made for CAL, resulted in being significantly reduced versus the inclusion. Nevertheless, the main goal of the present study was not merely focused on the already welldocumented efficacy of the one-stage full-mouth disinfection procedure (Morgandini et al, 1999;Quirynen et al, , 2006Aimetti et al, 2011;Swierkot et al, 2009;Teughels et al, 2009), when applied under the commonly used conditions. The hypothesis of the present study was that the application of a disinfection protocol consisting of tongue brushing and mouth rinsing with chlorhexidine-based products during two weeks prior to SRP would (1) reduce BoP at the time of SRP, (2) improve clinical parameters related to periodontitis, and (3) provide for improvement of periodontal tissue conditions up to three months and finally, (4) facilitate the clinicians in their job.…”
Section: Discussionmentioning
confidence: 99%
“…The percent value of lymphadenopathy-positive patients in daily treated group was twice of that weekly treated ones. Mongardini, et al [23] reported that half of the patients who underwent intensive subgingival instrumentation over a short period reported pyrexia over the following 12-24 hours as anecdotal evidence. Those reported changes in the above mentioned two studies could be attributed to systemic elevation of pro-inflammatory cytokines and acute-phase proteins.…”
Section: Discussionmentioning
confidence: 99%